2002
DOI: 10.1103/physrevb.66.020501
|View full text |Cite
|
Sign up to set email alerts
|

Antiferromagnetic ordering in a 90 K copper oxide superconductor

Abstract: Using elastic neutron scattering, we evidence a commensurate antiferromagnetic Cu(2) order (AF) in the superconducting (SC) high-$\rm T_c$ cuprate $\rm YBa_2(Cu_{1-y}Co_y)_3O_{7+\delta}$ (y=0.013, $\rm T_c$=93 K). As in the Co-free system, the spin excitation spectrum is dominated by a magnetic resonance peak at 41 meV but with a reduced spectral weight. The substitution of Co thus leads to a state where AF and SC cohabit showing that the CuO$_2$ plane is a highly antiferromagnetically polarizable medium even … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 35 publications
(85 reference statements)
2
34
2
Order By: Relevance
“…In most thermodynamic measurements for hole doped cuprates, AFLRO does not coexist with SC [12] and disappears completely around doping density d h~5 %. However, recent experiments such as muon spin rotation and elastic neutron scattering show that the spin density wave (SDW) may compete, or coexist with SC [13][14][15][16][17][18]. These results suggest that AFLRO may coexist with SC but the possibility of inhomogeneous phases is not completely ruled out.…”
Section: Introductionmentioning
confidence: 67%
“…In most thermodynamic measurements for hole doped cuprates, AFLRO does not coexist with SC [12] and disappears completely around doping density d h~5 %. However, recent experiments such as muon spin rotation and elastic neutron scattering show that the spin density wave (SDW) may compete, or coexist with SC [13][14][15][16][17][18]. These results suggest that AFLRO may coexist with SC but the possibility of inhomogeneous phases is not completely ruled out.…”
Section: Introductionmentioning
confidence: 67%
“…However, the polarization neutron analysis revealed that the order is dominated by moments aligned in the CuO 2 plane, as in the insulating parent compound. Considering, on the one hand, that other high-quality single crystals with a sim-ilar doping level do not show a similar order (123) and, on the other hand, that impurity substitution can induce antiferromagnetic order at 300 K even at optimal doping (124), it is likely that the observed AF order is not a generic property of the underdoped state. Subsequently, Mook et al (125) reported polarized neutron experiments suggesting the existence of a weak AF quasi-2d order with moments perpendicular to the CuO 2 plane.…”
Section: Spin Density Waves Seen By Neutron Diffractionmentioning
confidence: 99%
“…Recent experiments such as neutronscattering and muon spin rotation show that the spin density wave (SDW) may compete, or coexist with SC under the external magnetic field [4,5,6]. Remarkably, elastic neutron scattering experiments for underdoped Y Ba 2 Cu 3 O x (x = 6.5 and 6.6, T c = 55K and 62.7K, respectively) show that the commensurate AFLRO develops around room temperature with a large correlation length ∼ 100Å and a small staggered magnetization m 0 ∼ 0.05µ B [7,8,9]. These results suggest that AFLRO may coexist with SC but the possibility of inhomogeneous phases is not completely ruled out.…”
mentioning
confidence: 99%